Holding Space: A Roundtable Conversation on Trauma and Teaching in the Museum - DeLos Santos, Jenevieve; Lee, Kathleen Pierce with Key Jo; Martínez, Gabriela; Reaves, Damon; Scruggs, Dalila (Art Journal Open, 2021)
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas–from Nunavut to Tierra del Fuego. Through three themes–landscape, territory, and trade–this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."–Résumé de l'éditeur
Section: 223 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Collecting African American Art: the Museum of Fine Arts, Houston - Franklin, John Hope; Wardlaw, Alvia J (Museum of Fine Arts ; Yale University Press, 2009)
This important book showcases institutional and private efforts to collect, document, and preserve African American art in American's fourth largest city, Houston, Texas. Eminent historian John Hope Franklin's essay reveals his passionate commitment to collect African American art, while curator Alvia J. Wardlaw discusses works by Robert S. Duncanson, Henry Ossawa Tanner, Horace Pippen, and Bill Traylor as well as pieces by contemporary artists Kojo Griffin and Mequitta Ahuja. Quilts, pottery, and a desk made by an African American slave for his daughter contribute to the overview. The book also focuses on the collections of the "black intelligentsia," African Americans who taught at black colleges like Fisk University, where Aaron Douglas founded the art department. A number of the artists represented were collected privately before they were able to exhibit in mainstream museums.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Méthodologie de recherche décoloniale; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé